Evaluation of the immune colloidal gold technique for BP180-NC16A-specific antibodies in the quick diagnosis and monitoring of bullous pemphigoid. Issue 3 (December 2022) - Fan, Birao; Tang, Yuchen; Chang, Yuan; Chen, Xixue; Tu, Ping; Wang, Mingyue
Abstract: Background: Bullous pemphigoid (BP) mostly involves elderly patients. The diagnosis of BP requires special immunological tests, which makes some patients unable to be diagnosed and treated timely. Objective: The accuracy and application value of immune colloidal gold technique (ICGT) in BP were evaluated. The colloidal gold was conjugated with recombinant BP180 NC16A protein and mouse IgG antibody. As the test and control lines, the mouse-anti-human IgG and goat-anti-mouse IgG, respectively, were blotted on the nitrocellulose membrane. Methods: 414 serum samples of consecutive patients with suspected BP and 15 samples from healthy donors were recruited. The consistency between ICGT and ELISA, and between serum and plasma/whole blood were evaluated. Subgroup analyses were performed in terms of clinical characteristics. We also followed up 65 BP patients' strip results to explore the predictive value of ICGT. Results: Strong agreements between ICGT and ELISA(κ = 0.902) and between plasma/whole blood and serum samples (κ = 0.980) with good stability were observed. The ICGT achieved sensitivity of 93.9%, and specificity of 97.6%. In subgroup analysis, the sensitivity was significantly higher in older patients (96.3%), and with more typical lesions such as blisters (96.2%) and erosions (92.4%). In follow-up, we also found BP patients who kept ICGT-negative in remission state all got consecutive positive strips 1–3 weeks prior to mild new activity or flare. Conclusion: ICGT shows high potential as a rapid and stable option for the diagnosis and monitoring of BP. Further investigations are needed to re-evaluate this technique in a prospective study with a multicenter design. Highlights: Bullous pemphigoid (BP) mostly involves the elderly. Anti-BP180 NC16A IgG antibodies could be used for enzyme-linked immunosorbent assay (ELISA) in BP diagnosis. The level of anti-BP180 NC16A IgG parallels to the disease activity. The immune colloidal gold technique (ICGT) shows perfect concordance with the conventional ELISA in BP antibody detection. Compared with ELISA, ICGT has undeniable advantages: flexible, inexpensive, easy-to-operate and quick read-out. ICGT shows high potential as a rapid and stable option for the diagnosis and monitoring of BP.